US – MEXICAN RELATIONS UNDER PRESIDENTS DONALD TRUMP AND JOSEPH BIDEN (Вісник: Міжнародні відносини, 2021)
The article attempts to determine Mexico's place among US foreign policy interests under the administrations of Donald Trump and Joseph Biden. To this end, the priority areas of bilateral relations between the administrations of the US and Mexican governments have been identified Particular attention is paid to the place of the Latin American region in the system of American national interests. An analysis of the factors that influenced the formation of US policy towards Mexico and determines the nature of its qualitative changes during these periods. As a result of the study, the author concluded that the United States' policy toward Mexico and its place among foreign policy priorities is strategically important for Washington.
Keywords: USA, Mexico, Latin America, foreign policy. Biden, Andres Manuel Lopez Obrador, Trump, migration policy